Effect of chitosan coating on microemulsion for effective dermal clotrimazole delivery. (19th May 2017) - Kumari, Babita; Kesavan, Karthikeyan
Abstract: Clotrimazole (CTZ) is a broad spectrum antimycotic agent known to be very effective locally for the treatment of fungal skin infections. The aim of this study was to study the effect of chitosan-coated microemulsion (CME) for topical delivery of CTZ and also evaluate its in vitro antifungal efficacy, ex vivo permeation and retention ability on the skin surface. The pseudo-ternary phase diagrams were developed using clove oil as oil phase, Tween 80 and propylene glycol as surfactant and co-surfactant, respectively, and distilled water as aqueous phase. CME was prepared by the drop wise addition of chitosan solution to the optimized microemulsion. Physicochemical parameters (globule size, zeta potential, drug content, viscosity and pH) and in vitro release of CME were studied. The in vitro antifungal efficacy of CME and ME was studied by cup-plate method against Candida albicans. Ex vivo drug permeation study was also carried out in a modified diffusion cell, using rat skin. The developed CME displayed an average globule size less than 50 nm and a positive surface charge, acceptable physico-chemical behavior, and exhibited sustained drug release in in vitro study. In in vitro anti-fungal study, CME showed greater values of zone of inhibition as compared to ME due to its prolonged action as well as fungistatic nature of chitosan. In ex vivo study, CME showed better retention and sustained permeation property than ME due to the mucoadhesive property of chitosan. These results suggest that positively charged CMEs could be used as novel topical formulation for its ability to retain on the skin and its ability to sustain the release of the drug.